Sosialisasi Pembuatan Simanis Abang Ganteng (Sirup Manis Rimbang Kalimantan Tengah) sebagai Inovasi dan Potensi Sayuran Lokal - Zimon Pereiz; Chuchita Chuchita; Efriyana Oksal; Febrianto Afli; Ahmad Irawan; Miranti Maya Sylvani (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Many rimbang harvests, which are local vegetables from Central Kalimantan, are damaged and then thrown away because they are not marketable. This is clearly due to the relatively short shelf life of rimbang fruit. Farmers who depend on the harvest as their main source of income will certainly be disadvantaged by this. In addition, rotten rimbang vegetables will have a negative impact on the environment because they produce methane gas, one of the gases that causes global warming. So this community service program innovates rimbang, where rimbang is made into a syrup drink. Rimbang syrup can be a new innovation to create new products that are competitive, have high selling value, and are durable. The implementation of the community service program took place in the Habaring Hurung Village farmer group, Bukit Batu District, Palangka Raya City, Central Kalimantan Province. This activity program was carried out through 4 stages of activities, including location surveys, collection of raw materials, training in making eggplant dodol, and success indicators. The success indicators were carried out using the pre-test and post-test methods filled out by the activity participants in the form of a questionnaire. Based on the results of the activity, it can be concluded that this activity is able to increase insight and ability on how to make syrup with rimbang as the basic ingredient, even the residents can implement and apply this food innovation independently.